Effect of batch type scraped surface heat exchanger (SSHE) on Sensory attributes of Bottle gourd (Lagenaria siceraria) halwa - Jain, Sapna; Kartikeyan, S; Bhadania, AG (Indian Journal of Dairy Science, 2022)
The awareness among consumers for healthier and functional food has led to increase in the market size for valued added products. The present study was undertaken to manufacture valued added Indian indigenous dairy product, bottle gourd halwa in a multipurpose batch type SSHE. The performance of the developed SSHE was evaluated at three different steam pressures (1, 1.5 and 2 kg/cm2), scraper speeds (10, 20 and 30 rpm) by keeping batch size constant (5kg) during manufacturing of bottle gourd halwa. The products were evaluated for sensory characteristics with a 9-point Hedonic scale. The overall acceptability of the product was considered on the basis of sensory attributes. The bottle gourd halwa prepared in SSHE at 1kg/cm2 steam pressure and 30 rpm scraper speed (P1S3) had the score of 7.9 for flavour, 7.85 for body and texture and 7.4 for colour & appearance and the highest overall acceptabilityÂ  score (7.72) Â as compared to the products prepared at other operating conditions. However, it was not equivalent to control for these attributes.